Food choices and distress in reservation-based American Indians and Alaska Natives with type 2 diabetes. Issue 13 (23rd April 2018) - Teufel-Shone, Nicolette I; Jiang, Luohua; Rockell, Jennifer; Chang, Jennifer; Beals, Janette; Bullock, Ann; Manson, Spero M
Abstract: Objective: To examine the association between food choice and distress in a large national sample of American Indians/Alaska Natives (AI/AN) with type 2 diabetes. Design: Participants completed a sociodemographic survey, an FFQ and the Kessler-6 Distress Scale. Foods were identified as 'healthy' or 'unhealthy' using a classification grounded in the health education provided by the programme case managers; healthy and unhealthy food scores were calculated using reported intake frequencies. Pearson's correlation coefficients for distress and food scores were calculated for all participants and by gender. Multiple linear regression models stratified by gender assessed the association between distress and food scores, controlling for sociodemographics and duration of type 2 diabetes. Setting: Rural AI reservations and AN villages. Subjects: AI/AN ( n 2484) with type 2 diabetes. Results: Both males (34·9 %) and females (65·1 %) had higher healthy food scores than unhealthy scores. In bivariate analysis, distress level had a significant negative correlation with healthy food scores among female participants, but the association was not significant among males. Significant positive correlations between distress and unhealthy food scores were found in both genders. In the final multivariate models, healthy food scores were not significantly related to distress; however, unhealthy food scores showed significant positive relationships with distress for both genders (females: β =0·078, P =0·0007; males: β =0·139, P <0·0001). Conclusions: Health professionals working with AI/AN diagnosed with type 2 diabetes should offer food choice strategies during difficult times and recognize that males may be more likely than females to select unhealthy foods when distressed.